Capturing Value in the Internet of Things - Felix Wortmann; Dennis Herhausen; Dominik Bilgeri; Markus Weinberger; Elgar Fleisch (Marketing Review St.Gallen, 2020)
The Internet of Things (IoT) promises to deliver enormous business value. More specifically, IoT solutions disrupt existing business models by opening up novel service opportunities. In order to help companies understand the opportunities and challenges of this development, we shed light on different IoT revenue models. Based on an inductive case study approach, we identify nine direct and indirect revenue patterns. The different types of revenue patterns all use IoT-enabled services to create value for customers; the extent and the monetization of services, however, vary.
Keywords: 650